Frog on a log - Cox, Phil Roxbee; Cartwright, Stephen; Tyler, Jenny (Tulsa, Okla. : EDC, 2001)
Tired of being bumped off his log into the bog, Frog decides to strap himself to the log.
"A phonics reader"--Cover.
Lift-the-flap pages.
2.7.
2.7
K-3
Keywords: Toy and movable books -- Specimens; Frogs -- Fiction; Stories in rhyme; Toy and movable books; Frogs -- Fiction; Stories in rhyme; Toy and movable books